Various treatment modalities in aggressive periodontitis - Priya Dayashankar Chaurasia; Deepika Pawar Chandrashekara Rao; Eeshita Bhowmik (Wolters Kluwer Medknow Publications, 2019)
This is a case report of an 18-year-old female diagnosed with localized aggressive periodontitis. Following basic scaling and root planing, flap surgery was performed in all the four quadrants using various regenerative materials. A follow-up of 2½ years shows improvement in clinical and radiographic parameters, with no recurrence of the disease process.